2006
DOI: 10.1074/jbc.m601578200
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Role of the N-terminal Tail of the Na,K-ATPase Catalytic Subunit as a Signal Transducer

Abstract: Mounting evidence suggests that the ion pump, Na,KATPase, can, in the presence of ouabain, act as a signal transducer. A prominent binding motif linking the Na,K-ATPase to intracellular signaling effectors has, however, not yet been identified. Here we report that the N-terminal tail of the Na,KATPase catalytic ␣-subunit (␣NT-t) binds directly to the N terminus of the inositol 1,4,5-trisphosphate receptor. Three amino acid residues, LKK, conserved in most species and most ␣-isoforms, are essential for the bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(105 citation statements)
references
References 37 publications
4
99
0
2
Order By: Relevance
“…Needless to say, other possibilities may also be in play. For example, knockdown of Na/K-ATPase reduces the interaction between the Na/K-ATPase and IP 3 R, which may simply reduce the sensitivity of IP 3 R to IP 3 or change the channel opening properties as suggested previously (10). These issues have to be addressed in future studies.…”
Section: The Na/k-atpase Enhances the Efficiency Of Signal Transmissimentioning
confidence: 90%
See 3 more Smart Citations
“…Needless to say, other possibilities may also be in play. For example, knockdown of Na/K-ATPase reduces the interaction between the Na/K-ATPase and IP 3 R, which may simply reduce the sensitivity of IP 3 R to IP 3 or change the channel opening properties as suggested previously (10). These issues have to be addressed in future studies.…”
Section: The Na/k-atpase Enhances the Efficiency Of Signal Transmissimentioning
confidence: 90%
“…2ϩ Release-Results from recent studies indicate that the N terminus of the Na/K-ATPase ␣1 subunit binds to IP 3 R directly (9,10). To detect whether the effect of Na/K-ATPase on ER Ca 2ϩ release is because of the direct interaction between Na/K-ATPase and IP 3 R, we constructed a YFP fusion protein containing the ␣1 N terminus (amino acids 1-160) (␣NT-eYFP).…”
Section: The N Terminus Of the Na/k-atpase Functions As A Dominant Nementioning
confidence: 99%
See 2 more Smart Citations
“…The idea of ionic transport proteins such as exchangers or co-transporters as signal transducers during apoptosis has recently been demonstrated for the Na + , K + -ATPase by Zhang et al [77]. Here the authors showed the direct interaction of the N-terminal tail of the catalytic α-subunit of the Na + , K + -ATPase with the N-terminus of the inositol 1,4,5-triphosphate receptor.…”
Section: Potassium As a Signal For Apoptosismentioning
confidence: 91%